2017
DOI: 10.1002/ajmg.b.32518
|View full text |Cite
|
Sign up to set email alerts
|

miR‐149 and miR‐29c as candidates for bipolar disorder biomarkers

Abstract: Bipolar disorder (BD) is a common, recurring psychiatric illness with unknown pathogenesis. Recent studies suggest that microRNA (miRNA) levels in brains of BD patients are significantly altered, and these changes may offer insight into BD pathology or etiology. Previously, we observed significant alterations of miR-29c levels in extracellular vesicles (EVs) extracted from prefrontal cortex (Brodmann area 9, BA9) of BD patients. In this study, we show that EVs extracted from the anterior cingulate cortex (BA24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…The authors of the present study hypothesized an association between BMP-2 and postmenopausal osteoporosis, and miRs that may regulate BMP-2 were investigated in the present study. Previous studies have identified a number of miRs as biomarkers for different diseases (39,40). In the current study, bioinformatics tools were utilized to identify upstream genes predicted to regulate BMP-2, which resulted in the identification of miR-410 as a potential upstream regulator.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the present study hypothesized an association between BMP-2 and postmenopausal osteoporosis, and miRs that may regulate BMP-2 were investigated in the present study. Previous studies have identified a number of miRs as biomarkers for different diseases (39,40). In the current study, bioinformatics tools were utilized to identify upstream genes predicted to regulate BMP-2, which resulted in the identification of miR-410 as a potential upstream regulator.…”
Section: Discussionmentioning
confidence: 99%
“…The histological studies on glial cell loss are supported by the recent molecular findings on altered microRNA (miRNA) levels in the brains of BD patients. For example Choi et al ( 2017 ) extracted extracellular vesicles from the PFC (Brodmann area 24) and found increased levels of miR-149 exclusively in glial cells. Since miR-149 can inhibit glial cell proliferation thus, increased miR-149 expression might contribute to the glial cell number reduction.…”
Section: Cellular Evidences For Glial Pathologymentioning
confidence: 99%
“…This suggests changes in miRNA may underlie fundamental dysregulated pathways in mood disorders. Recent studies have also highlighted the importance of extracellular vesicles, such as exosomes and microvesicles, in the CNS or in the periphery in individuals with mood disorders, most notably in BD [38][39][40]. Such vesicles can traffic aberrantly expressed miRNA between cells, effectively regulating RNA translation in nearby cells.…”
Section: Micro Rna In Mood Disordersmentioning
confidence: 99%